Accuracy of the KOH and vancomycin tests in determining the Gram reaction of non-enterobacterial rods. - von Graevenitz, A (1983)
Two nonstaining tests for the Gram reaction, the KOH and vancomycin disk (5 micrograms) tests, were employed on 488 strains of aerobic gram-negative and gram-positive rods. Since each test may yield false results with certain species, the use of a combination is suggested.